Suggestions for reforming the governance of global accounting standards - Nicolas Véron (Bruegel, 2011)
Public authorities overseeing the International Financial Reporting Standards (IFRS) Foundation, through the Monitoring Board in place since early 2009, should encourage the Foundation to make itself more directly accountable to the global investment community. The Monitoring Board should re-examine its own role, composition and processes in the same spirit, one option being its enlargement to include investor representatives, and transformation into a statutory body of the IFRS Foundation. The IFRS Foundation's funding framework should be better aligned with its governance and accountability arrangements. This Policy Contribution is an adaptation of a letter sent on 12 April 2011 from the author to the Monitoring Board of the IFRS Foundation, whose members are public authorities including the European Commission, as a response to the public consultation on the Monitoring Board's Consultative Report on the review of the IFRS Foundation's governance.
Keywords: 330; Bilanzpolitik; Globalisierung; Normung; Politische Reform; Welt